Copula + Adjective: An a-posteriori power analysis for the generalizability of results. (12th July 2018) - Aguilar-Sanchez, Jorge
Abstract : Researchers sometimes, unknowingly, exclude the existence of the phenomenon in the population under study to develop investigations that try to explain discrepancies observed in the literature. Explanations justifying each study are based on theories; or conjecture related to specific independent variables and how researchers disagree with the construct proposed originally. These disagreements create variants of the original study, but not proper replications of it. This practice produces what Ottenbacher (1996: 275) called 'a contradictory research literature, apparently dynamic, but failing to resolve uncertainties; therefore, failing to establish statistical consensus'. To resolve these uncertainties, this paper addresses the concerns that arise by not reporting two statistics: power and effect size. Power calculations were conducted for the studies on copula choice in bilingual Spanish. Results show that studies have a low power due to decisions that were made during their design, or due to the aggregation of naturally independent data. due to the aggregation of naturally independent data.